(untitled) (Al-Qamar, 2021)
Qazi Sanaullah Pani Patti was one of the eminent scholars of subcontinent. He belonged to the Mujaddidi order of Sufism, which is the main branch of Naqshbandi Sufi tariqah. He was the author of many books. One of the major contribution by Qazi Sanaullah is in the field of Tafseer. He wrote a famous tafseer on the name of one of his teachers Mazhar Jane Janan. Name of the tafseer is “Tafseer e Mazhari”. In the given research article I have discussed the ways Qazi Sanaullah prefers opinions of some scholars over opinions of other scholars in his tafseer. As rules of preferences is a great concern for those interpreting the words of Quran because this requires careful consideration and thought in the context of different opinions, and linking them to reach a conclusion, similarly it necessitates for the exegetes that these rules be in the light of Quran and Sunnah and not their personal opinions. This research paper discusses the ways of preference used by Qazi Sanaullah.